Muscle oxygen saturation rates coincide with lactate-based exercise thresholds - Batterson, P. M.; Kriby, B. S.; Hasselmann, G.; Feldmann, A. (European Journal of Applied Physiology, 2023)
Introduction Monitoring muscle metabolic activity via blood lactate is a useful tool for understanding the physiological response to a given exercise intensity. Recent indications suggest that skeletal muscle oxygen saturation (SmO2), an index of the balance between local O2 supply and demand, may describe and predict endurance performance outcomes.